MANFAAT E-BUSINESS BAGI PERUSAHAAN (Studi Kasus Pada Laman Website Furniture) - AMELIA SETYAWATI (STIE Indonesia Malang, 2021)
Information and communication technology indeed continues to bring a change and a significant impact in our daily lives. Of course, the community and business people continue to adapt on a large scale to all lines, in this case, especially the business sector. This change in doing business has finally shifted buying and selling trends between businesspeople to consumers or vice versa. Based on this phenomenon, the application of the concept of e-business is considered to provide many benefits in business activities. Interestingly, this e-business has become a driving force for the current digital transformation process. Of course, all the rapid changes that occur are related to the existence of e-business which is currently widely used. So it is not surprising that nowadays, people are competing to innovate to prioritize further all things that support the existence of this e-business.Some perceived benefits are a lot, especially for a company. This article describes some of the direct benefits of business people and consumers that can be described through a website for a start-up company that sells furniture. With digital technology and e-business, this company has increased profits and introduced new experiences in buying furniture. In the past, buying furniture was considered a waste of time and shipping costs, now this problem has been successfully answered by this company.Keywords: e-business, benefit, company